graph-GPA 2.0: improving multi-disease genetic analysis with integration of functional annotation data - Deng, Qiaolan; Gupta, Arkobrato; Jeon, Hyeongseon; Nam, Jin Hyun; Yilmaz, Ayse Selen; Chang, Won; Pietrzak, Maciej; Li, Lang; Kim, Hang J.; Chung, Dongjun (Frontiers in Genetics, 2023)
Genome-wide association studies (GWAS) have successfully identified a large number of genetic variants associated with traits and diseases. However, it still remains challenging to fully understand the functional mechanisms underlying many associated variants. This is especially the case when we are interested in variants shared across multiple phenotypes. To address this challenge, we propose graph-GPA 2.0 (GGPA 2.0), a statistical framework to integrate GWAS datasets for multiple phenotypes and incorporate functional annotations within a unified framework. Our simulation studies showed that incorporating functional annotation data using GGPA 2.0 not only improves the detection of disease-associated variants, but also provides a more accurate estimation of relationships among diseases. Next, we analyzed five autoimmune diseases and five psychiatric disorders with the functional annotations derived from GenoSkyline and GenoSkyline-Plus, along with the prior disease graph generated by biomedical literature mining. For autoimmune diseases, GGPA 2.0 identified enrichment for blood-related epigenetic marks, especially B cells and regulatory T cells, across multiple diseases. Psychiatric disorders were enriched for brain-related epigenetic marks, especially the prefrontal cortex and the inferior temporal lobe for bipolar disorder and schizophrenia, respectively. In addition, the pleiotropy between bipolar disorder and schizophrenia was also detected. Finally, we found that GGPA 2.0 is robust to the use of irrelevant and/or incorrect functional annotations. These results demonstrate that GGPA 2.0 can be a powerful tool to identify genetic variants associated with each 1 Deng et al.graph-GPA 2.0 phenotype or those shared across multiple phenotypes, while also promoting an understanding of functional mechanisms underlying the associated variants. R package 'GGPA2' is available at https://dongjunchung.github.io/GGPA2/.